Studies in the Aramaic legal papyri from Elephantine - Muffs, Yochanan. (Handbook of Oriental Studies. Section 1 The Near and Middle East, 2002)
Long recognized as a brilliant cross-cultural study, Yochanan Muffs' work analyzes the legal formulary of the Aramaic papyri from Elephantine, at the first cataract of the Nile, where a Persian garrison comprised of Jewish soldiers and their families lived throughout most of the 5th century B.C.E. These documents are of exceptional importance for the study of ancient Near Eastern law, and Muffs has investigated their formative background through extensive references to cuneiform law, by a method he calls "the Assyriological approach". Virtually every aspect of law-sale of land, marriage and family law, loans and credit, the taking of oaths, and the granting of bequests is studied in great depth and with unusual clarity. Muffs' work has enjoyed renewed interest in the light of more recent discoveries of Aramaic legal documents from later periods, as in the Judean Desert.